2019
DOI: 10.15405/epsbs.2019.11.65
|View full text |Cite
|
Sign up to set email alerts
|

Typology Of Czech University Students By Their Internet Addiction

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Excellent internal consistency (Cronbach's alpha of 0.93) of the CIAS-R scale was achieved in our pilot research. This result was similar to that one reached by Chraska (2019) in his pilot study which focused on revealing Internet addiction of Czech university students, and which applied CIAS.…”
Section: Pilot Studysupporting
confidence: 89%
See 2 more Smart Citations
“…Excellent internal consistency (Cronbach's alpha of 0.93) of the CIAS-R scale was achieved in our pilot research. This result was similar to that one reached by Chraska (2019) in his pilot study which focused on revealing Internet addiction of Czech university students, and which applied CIAS.…”
Section: Pilot Studysupporting
confidence: 89%
“…'This can be caused by specific features of teacher training.' (Chraska, 2019: 562) The number of other studies dealing with this group of students is not high, but referring to the data available (Demirer, Bozoglan and Sahin, 2013;Chraska, 2019), we can claim that the level is comparable. Personal experience that the students of faculties of education have with Internet addiction is a topic that seems very important, especially with regard to their future teaching career and their role in prevention of risky behavior, or specifically in prevention of Internet addiction.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The scale consisted of 20 items with the following answers: not applicable-−0, rarely-−1, occasionally-−2, frequently-−3, often-−4, always-−5. Internet addiction was identified as follows: normal level of internet usage (0-30), mild addiction symptoms (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), moderate addiction symptoms , and severe addiction symptoms (80-100). The IAT scale was composed of six subscales for which precise interval thresholds are not defined.…”
Section: Methodsmentioning
confidence: 99%
“…In Slovakia, Sebena et al (44) highlighted the seriousness of problematic internet use among college students and confirmed that depressive symptoms predict their problematic internet use. In the Czech Republic, the issue was addressed by Chraska (45). In both countries, however, the research focus was mainly on primary and secondary school students (46)(47)(48).…”
Section: Introductionmentioning
confidence: 99%